The (im)possibility of forgiveness? An empirical intercultural Bible reading of Matthew 18:15-35 - Forster, Dion (African Sun Media, 2017)
"This book deals with contested and topical matters. Biblical hermeneutics has always been contested - how to read and understand Biblical passages. Things become even more contested when such passages are read inter-culturally; they become even more contested when the words are about contested personal and social issues, like Jesus' words on forgiveness in Matthew 18. Empirical studies like this show how deeply contested such readings truly are in the context of South African churches, with their painful histories of division and conflict. Future academic work will, therefore, benefit from the creative and careful methodological approach developed in this study. However, this book offers much more than academic promise - precisely because of the theme, so topical today and without doubt topical for a long time to come and in many other places in our contemporary world as well. Forster offers resources for reading and conversation for everyone concerned with public life today. This is public theology in action, showing how faith matters - without prescribing answers, but rather by invitation to join an informed discussion." - Dirk J Smit, The Rimmer and Ruth deVries Professor of Reformed Theology and Public Life, Princeton Theological Seminary